Lessons from Phenology: an Interim Report - Harper, Geoffrey (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2010)
Twenty provisional multiple-regression models based on a small data set are presented to account for the timing of first-flower date and other phenological events. Biological mechanisms are suggested to explain the pattern of temperature-dependent developmental stages. The implications for how plants and vegetation are likely to react to climate change are discussed, and attention is drawn to the importance of within-taxon variation in phenological behaviour.